The Factor Structure Referring to “The Dark Figures of Crime” - Gojković, Vesna; Fajgelj, Stanislav (Zbornik Instituta za kriminološka i sociološka istraživanja, 2006)
The research on The structure of the factors referring to “the dark figures of the crime” is a part of a wider study that deals with the relation of the type of the violent crime and the personality of the criminal. In this report, the main task was to use the factors’ analysis results of the TBR test to find the latent ways of deviant and delinquent behavior that produce violent delicts. The aim of the research was to find out whether there was a difference in the structure of the crime when it was defined as a judgment criminality, that is, when the analysis was conducted on the basis of the undiscovered crimes. We supposed that the difference would be defined by the influence of the drug addiction of the convicts. 356 men convicted of murders, robbery, causing aggravated assault and battery and rapes were interrogated using the scale for measuring the undiscovered crimes TBR. Seven main factors were extracted by the factors’ analysis, but although the important existence of the drug addiction was confirmed, the percentage of the solved variance doesn’t allow us to prove the stated hypothesis scientifically.